Island differentiation of New Zealand’s extinct mergansers (Anatidae: Mergini), with description of a new species from Chatham Island: correction and addition - Williams, Murray; Tennyson, Alan J.D.; Sim, Dalice (Wildfowl, 2015)
An ambiguous designation of the holotype of Chatham Island Merganser Mergus milleneri is corrected, and an overlooked discovery of a bone of this merganser associated with a Polynesian midden dating from the early 16th Century is appraised.